IMPLEMENTATION OF FAMILY-BASED CHARACTER EDUCATION FOR YOUNG GENERATIONS IN LAU GUMBA VILLAGE BERSTAGI DISTRICT KARO REGENCY - Muhammad Yunan Harahap (Proceeding International Seminar of Islamic Studies, 2022)
Implementation of family-based character education is not an easy thing for parents to do. Because, after Covid-19, many young people, especially high school students, have been poisoned by online games. Nowadays, almost all young people have gadgets and many of them use it incorrectly so that it affects behavior change. This study aimed to: 1. Find out how parents implement character education for the younger generation in Lau Gumba Village, Berastagi District, Karo Regency. 2. Knowing the supporting and inhibiting factors for implementing family-based character education for the younger generation. The method used in this research was descriptive qualitative method. The results of the study indicated the implementation of family-based character education in Lau Gumba Village, namely: 1. Parents exemplified the spirit of work and responsibility. 2. Parents Cultivated humility. 3. Parents became example in carrying out religious worship. The supporting factors were a strong spirit and motivation in educating children, while the inhibiting factor was a lack of understanding of character education in the family.Keywords: Implementation, Character Education, Family Based